Permissivism and the Debate About Universals - Rossi-Fernandez, C (Routledge, 2025)
Permissivism is a view about ontological questions which holds that such questions for the most part can all be trivially answered. Understood in this way, Permissivism seems to be entailed, or at least motivated by, an important number of ontological and metaontological views, ranging from Mereological Universalism and Material Plenitude to ontologies which draw prominently on some notion of fundamentality, and Deflationism. By and large, permissivist-inspired arguments have had as their ontological target material objects, but little to none is found within the ontological debate about properties. Our aim in this paper is to address this omission by providing a thorough assessment of one notable effort in this direction formulated by Jonathan Schaffer, which defends the existence of universal properties by way of trivial inferences. We argue that such inferences fail to secure the existence of universal properties in a trivial manner. Together with offering an extended discussion of Schaffer’s permissivist inferences, we also explore alternative ways in which the said inferences can be amended, although in each case with a restricted scope. © 2025 Informa UK Limited, trading as Taylor & Francis Group.